Ethnobotanical Study on Traditional Wedding Ceremonies in Nagari Koto Malintang Agam Regency, West Sumatra - Febby Andesla Febrian; Filza Yulina Ade; Moralita Chatri; Yusni Atifah (Jurnal Biologi Tropis, 2026)
Local community knowledge about the utilization of plants in traditional ceremonies is a cultural heritage that is vulnerable to extinction due to modernization. Koto Malintang Village, located in the Lake Maninjau area, Agam Regency, West Sumatra, still strongly adheres to customs and traditions but has not been scientifically documented regarding the use of plants in its traditional ceremonies. This study aimed to identify the plant species, plant parts used, and how they are utilized in traditional wedding ceremonies in Koto Malintang Village. This descriptive research with qualitative and quantitative approaches was conducted from December 2025 to April 2026. Data collection was carried out through semi structured interviews with 20 key informants consisting of panghulu, bundo kanduang, niniak mamak, community members involved in ceremonial processes, and elders, as well as direct observation and documentation. Data analysis used Use Value (UVs), Relative Frequency of Citation (RFC), and Plant Part Value (PPV). The results found 35 plant species from 20 families utilized in wedding ceremonies. The Zingiberaceae family was the most dominant. Leaves had the highest percentage of utilization (29,27%). The highest UVs value was found in turmeric rhizome (Curcuma longa L.) at 3,50 and the highest RFC value was found in betel (Piper betle L.) at 1,00. Plants are used as traditional equipment and traditional food ingredients. This study documents the richness of local ethnobotanical knowledge that needs to be preserved and serves as a basis for further research.